THE IMPACT OF LABOUR MARKET ON THE HUMAN RESOURCE MANAGEMENT IN GEORGIA - Kvirkvaia, Murtaz (European Scientific Journal, ESJ, 2014)
Labor market and human resource management are urgent issues for social sphere of Georgia. Majority of employees in Georgia consider they can be easily replaced by employers. Reality the current Georgian Labor market faces, respectively a high unemployment level, inefficient career planning, low level of revenues and salaries, no competition among employers to attract and recruit required personnel serve as the prerequisite to the fact that employers do not see HR as the major factor of their success, therefore they do not use contemporary approaches and trends of Human Resource Management. Implementation of modern technologies of HR management stipulates successful operation of separate organizations as well as encourages solutions to complicated social problems existing in the country.